Spring according to Humphrey - Birney, Betty G. (Birney, Betty G. Humphrey adventures, 2016)
"To Humphrey and the students at Longfellow School, spring seems impossibly late this year. Fortunately, planning a school Family Fun Night keeps the students (and classroom pets) busy as they look for signs of the changing seasons"--